Features of development of Lithuanian high mathematics terms - Pekarskas, Vidmantas; Pekarskienė, Aldona (Lietuvos matematikos rinkinys, 1997)
The development of wildly used Lithuanian terms in Analytical Geometry, Mathematical Analysis. Probability theory and Set theory is presented. The accent is made on their changes from little terms dictionaries by M. Šikšnys and Z. Žemaitis, printed in 1919 and 1920, till the "Dictionary of Mathematical Terms", printed in 1994.